Eigentlich bin ich ein bisschen dazu gekommen, wie die Jungfrau zum Kind : Zum Professionsverständnis von deutschen Berufsbildungsexperten im Ausland - Bakirci, Büsra [Verfasser]; Pilz, Matthias [Verfasser] (My University, 2019)
"In the course of globalization and the training needs in many countries, German VET cooperation is at the center of political interest. In particular, the transfer of elements of the German dual training system is discussed. The so-called vocational training experts who plan, control and also implement the transfer in the partner countries have not been particularly researched so far. Therefore, this article explores how the professional understanding of these German VET experts is constructed. By means of an interview survey of 13 vocational training experts working for many years abroad, a very complex competence profile could be generated from the perspective of those affected. The extensive findings document the great need for a systematic and institutionally anchored professionalisation strategy in order to optimize vocational training cooperation in the long term." (Authors' abstract, BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; Bildungstransfer; Bildungspersonal; Professionalisierung; Internationale Zusammenarbeit